Some aspects of thermal resistance measurement technique for IMPATT and light-emitting diodes - Belyaev, A.E.; Boltovets, N.S.; Konakova, R.V.; Kudryk, Ya.Ya.; Sorokin, V.M.; Sheremet, V.N.; Shynkarenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Some aspects of measuring the thermal resistance to a constant heat flow at a p-n junction–package region in IMPATT and light-emitting diodes are considered. We propose a method of studying the thermal resistance of high-power light-emitting diodes. This method makes it possible to increase accuracy of measuring the thermal resistance by determining the temperature at a linear section of the voltage−temperature curve. A possibility to measure the thermal resistance of IMPATT diodes by using the pulse I-V curves is shown. This enables one to simplify calculations and increase accuracy of measuring the thermal resistance.